Upaya Meningkatkan Hasil Belajar Pendidikan Agama Katolik (PAKAT) dengan Model Pembelajaran Kooperatif Round Club Peserta Didik Kelas IV SD Negeri 64/IV Kota Jambi - Elseria Sirait (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The study used two-cycle class action research. The target of this research is class IV students at SD Negeri 64/IV Jambi City. Data obtained in the form of formative test result, observation sheet of teaching learning activities. From the results analysts gained that the learning outcomes of learners experienced an increase from the pre cycle to the II cycle, the pre-cycle (47.5%), cycle I (70%) and cycle II (93.75%). The conclusion of this research is the Model of cooperative learning type Round Club can positively affect the outcome of students learning outcomes of Class IV elementary School 64/IV Jambi City, as well as this learning Model can be used as one alternative Study of Catholic religious Education.